The effect of static and dynamic balance exercises on developing some artistic gymnastic skills for female students of the College of Physical Education and Sports Sciences - Shihab , Sabreen (Journal of Physical Education, 2025)
The aim of the research is to identify the effect of using static and dynamic balance exercises in developing some technical gymnastics skills for female students of the Faculty of Physical Education and Sports Sciences. The research community consisted of second-year female students, while the research sample was chosen intentionally, and they are Section (B), numbering 20, female students, who were distributed into two groups (experimental - control), with 10 female students for each group. The researcher used the experimental method with a design of the experimental and control groups with pre- and post-tests, after applying the exercise components in the main experiment with 20 training units that lasted for 10 weeks. The results showed that there were significant differences in favor of the training group that used static and dynamic balance exercises